Cien años de soledad - Pusma Salazar, Clever (2020)
His work of professional sufficiency has as reference the work "One Hundred Years of Solitude" specifically one of the fragments it contains, whose purpose will be to analyze the corresponding content (theme, events and characters with their characteristics) this session is aimed at students Develop and analyze the fragment of the work. Likewise, reading is encouraged in the student, who at the same time recognizes some of the contents of the work so that he understands and infers correctly. These elements will be addressed during the class session reinforcing the understanding and appreciation of Spanish-American literature